2022
DOI: 10.3389/fsurg.2022.919744
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Following Single-Port Appendectomy: A Systematic Review of the Literature and Meta-Analysis

Abstract: IntroductionSurgical site infections (SSIs) are one of the most common postoperative complications after appendectomy leading to recurrent surgery, prolonged hospital stay, and the use of antibiotics. Numerous studies and meta-analyses have been published on the effect of open versus conventional laparoscopic appendectomy (CLA) reporting faster postoperative recovery and less postoperative pain for CLA. A development from CLA has been the single-port appendectomy (SPA), associated with a better cosmesis but se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The incidence of PSI is quite variable from one study to another. [14][15][16] Differences among the studies can be attributed to differences in the population, infection control and sterilization techniques that could differ from place to place. The incidence of PSI in our study is higher than that reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PSI is quite variable from one study to another. [14][15][16] Differences among the studies can be attributed to differences in the population, infection control and sterilization techniques that could differ from place to place. The incidence of PSI in our study is higher than that reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al ( 23 ) conducted a meta-analysis of 12 pediatric appendectomy procedures and found that compared with THLA, SILA significantly shortened the hospitalization time, but there was no significant difference in surgical time or other aspects. A meta-analysis conducted by Köhler et al ( 24 ) included a total of 20 studies, and the results showed that extracorporeal SILA seemed to have the advantage of a shorter surgical time, while in vitro / in vivo SILA showed no significant difference in safety compared to THLA. Aly ( 25 ) found that traditional laparoscopic appendectomy is significantly better than SILA in terms of surgical time and intraoperative conversion rate.…”
Section: Discussionmentioning
confidence: 99%
“…26 Garijo et al 32 reported using a 1.5-cm concealed transverse incision on the pubic bone that provided a good surgical field. Although single-port laparoscopic surgery has been shown not to increase the risk of surgical site infection, 38 its long-term cosmetic outcome remains controversial and needs to be validated in long-term follow-up studies. 39 Lowering surgical cost may reduce the economic burden of patients and improve cost-effectiveness.…”
Section: Optimal Surgical Treatment Strategy For Patients With Acute ...mentioning
confidence: 99%